(untitled) (Revista de História da UEG (REVHIST), 2020)
Abstract: In this article, we aim to trace a trajectory of the Roman Catholic Apostolic Church (ICAR) in the north of Rio Grande do Sul. In this sense, by way of context, we will examine the ethnic-cultural formation of such region, besides, of course, treating about the first contacts between the region and the ICAR. Our emphasis, though, will be the period known as the First Republic (1889-1930). Such emphasis is justified by the great transformations in ICAR in Brazil in this period, and because it was by the time of the First Republic’s end that the first commentaries about the creation of a dioceses in Passo Fundo came about. We shall use as documentais sources the Register Books of the parish of Nossa Senhora da Conceição Aparecida – the first parish in the north of the state of Rio Grande do Sul – situated in the city of Passo Fundo. In this sense, this work aims to give a historiographical contribution about ICAR in Rio Grande do Sul, as studies focused on such time and place are extremely sparse. Keywords: Religions. Religiosities. Roman Catholic Church. Rio Grande do Sul. Registry Books. History. Region.